Price Perception, Social Media Marketing, Dan Product Completeness, Terhadap Purchasing Decisions At The Paras Cantik Cosmetics Store - Ni Luh Nurkariani; Made Ari Sudewi (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the influence of Price Perception, Social Media Marketing, and Product Completeness at the Paras Cantik Cosmetics Store. This research employed a quantitative approach using a survey method. The sample consisted of 75 respondents selected through yhe accidental sampling technique. Data were collected using questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination with the assistance of IBM SPSS software. The results indicate that Price Perception has a positive and significant effect on Purchasing Decisions with a significance value of 0.001 < 0,05. Social Media Marketing also has a positive and significant effect on Purchasing Decisions with a significance value og 0,008 < 0,05. Meanwhile, Product Completeness has no significant effect on Purchasing Decisions, with a significance value of 0,812 > 0,05. Simultaneously, the three independent variabel have a significant effect on Purchasing Decisions, as indicated by an F-value of 15,311 and a significance value of 0,000 < 0,05. The Adjusted R Square value of 0,367 indicates that 36,7% of the variation in Purchasing Decisions is explained by the three independent variables, while the remaining 63,3% is influenced by other variables outside the scope of this study